2019
DOI: 10.1016/j.adro.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Single- Versus Multiple-Fraction Radiation Therapy for Painful Bone Metastases: A Systematic Review and Meta-analysis of Nonrandomized Studies

Abstract: PurposeSingle-fraction radiation therapy (RT) is a convenient and cost-effective regimen for the palliation of painful bone metastases, but is still underused. Randomized controlled trials comparing single- versus multiple-fraction RT are limited by generalizability. We compared the pain response rates after single- versus multiple-fraction RT in nonrandomized studies.Methods and MaterialsWe searched PubMed and Scopus from the inception of each database through August 2018. We sought to identify nonrandomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…38 This is convenient and cost-effective, yet still underused. [39][40][41] In our study, fewer patients had singlefraction treatments, similar to results from a recent Ethiopian study. 42 Several reasons may justify the choice of longer fractionation.…”
Section: Discussionsupporting
confidence: 90%
“…38 This is convenient and cost-effective, yet still underused. [39][40][41] In our study, fewer patients had singlefraction treatments, similar to results from a recent Ethiopian study. 42 Several reasons may justify the choice of longer fractionation.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that randomised studies and meta-analyses do not show any superiority between these treatment regimens in the management of uncomplicated bone metastases. Moreover, they show that the hypofractionated regimen was more commonly used by experienced radiotherapists [13], [16], [17], [14]. The study by Slotman et al showed that the majority of patients preferred a one-day management [18].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is an important treatment option for cancer-related pain [1,2]. The pain response rate after radiotherapy for painful various tumors was reportedly 47-80% [3][4][5][6]. Among them, radiotherapy for painful bone metastases, which has been investigated extensively [3,6,7], was strongly recommended by the World Health Organization [8].…”
Section: Introductionmentioning
confidence: 99%
“…The pain response rate after radiotherapy for painful various tumors was reportedly 47-80% [3][4][5][6]. Among them, radiotherapy for painful bone metastases, which has been investigated extensively [3,6,7], was strongly recommended by the World Health Organization [8]. However, there are few studies of palliative radiotherapy for painful tumors other than bone metastases [9].…”
Section: Introductionmentioning
confidence: 99%